2018
DOI: 10.1016/j.ijid.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Parallel susceptibility testing of bacteria through culture-quantitative PCR in 96-well plates

Abstract: With rapidness to obtain results and the capabilities for automation and multiple-sample testing, the parallel culture-qPCR method would have great potentials in clinical labs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The use of the universal BactQuant 16S amplification system simplified the assay, requiring only a single set of primers and probes for testing of all bacterial pathogens. Further improvement of this assay could be achieved through the application of recently reported thermo-cold lysis for DNA extraction, potentially decreasing hands-on time and operator error [21]. Overall, our assay showed high categorical agreement at 96.3% while representing a significant decrease in total assay time compared to a similar qPCR AST assay from blood culture.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The use of the universal BactQuant 16S amplification system simplified the assay, requiring only a single set of primers and probes for testing of all bacterial pathogens. Further improvement of this assay could be achieved through the application of recently reported thermo-cold lysis for DNA extraction, potentially decreasing hands-on time and operator error [21]. Overall, our assay showed high categorical agreement at 96.3% while representing a significant decrease in total assay time compared to a similar qPCR AST assay from blood culture.…”
Section: Resultsmentioning
confidence: 85%
“…Bacterial strains susceptible to the given antibiotic will display growth inhibition resulting in significantly lower concentrations of nucleic acid, measurable by quantitative PCR (qPCR) or other amplification technologies [18]. Previous studies utilizing this approach showed promising results with high levels of categorical agreement with gold standard assays [1821]. In fact, the method adequately determined susceptibility across multiple classes of antibiotics and was applicable to a variety of bacterial pathogens depending on the primer (and probe) design [19, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the method can be applied for antibiotics-resistant detection through directly culturing the sputum samples with antibiotics for 1 or 2 hours, [28,29] and then the amount of the bacteria will be different for drug-sensitive and drug-resistant bacteria. Otherwise, there cases of pulmonary infection based on phage therapy are increasing [30,31] and this method provides ideas for phage screening and monitoring in phage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A new generation of nucleic acid amplification tests (NAATs) can measure species-specific growth rates of bacteria in the original sample in response to different antibiotics (Rolain et al, 2004;Maxson et al, 2018). These tests require ∼2-4 h of in vitro incubation, which would be a significant improvement in turnaround time (Luo et al, 2018). Furthermore, the current operative cost of these PCRbased tests can be below equivalent cost related to traditional plate-based tests.…”
mentioning
confidence: 99%